1978
DOI: 10.1159/000155856
|View full text |Cite
|
Sign up to set email alerts
|

Continual Sexual Receptivity in the Female Chimpanzee (Pan troglodytes)

Abstract: Daily observations during a 5-year period showed that the mean frequencies of copulation per day during various sexual states of the female chimpanzee were almost identical, except for during maximum tumescence and lactation. The mean frequency of observed copulation peaked during maximum tumescence and was lowest during lactation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…One behavioral category in which pregnant and cycling females did not differ was sexual interaction; as in menstrual cycles, anogenital swelling during chimpanzee pregnancy was associated with sexual activity [Wallis & Lemmon, 19861. These results were similar to previously published data for chimpanzee populations both in the wild [van Lawick-Goodall, 1969;Nishida, 1979;Tutin & McGinnis, 19811 and in captivity [Tinklepaugh, 1933;Yerkes, 1939;Lemmon & Allen, 1978;Wallis, 19821.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…One behavioral category in which pregnant and cycling females did not differ was sexual interaction; as in menstrual cycles, anogenital swelling during chimpanzee pregnancy was associated with sexual activity [Wallis & Lemmon, 19861. These results were similar to previously published data for chimpanzee populations both in the wild [van Lawick-Goodall, 1969;Nishida, 1979;Tutin & McGinnis, 19811 and in captivity [Tinklepaugh, 1933;Yerkes, 1939;Lemmon & Allen, 1978;Wallis, 19821.…”
Section: Introductionsupporting
confidence: 92%
“…The period of anogenital swelling, particularly when maximal, is associated with both female-and male-initiated sexual behavior [Yerkes & Elder, 1936;Yerkes, 1939;van Lawick-Goodall, 1969;Lemmon & Allen, 1978;Nishida, 1979;Tutin & McGinnis, 1981;Wallis, 1982. Pregnant female chimpanzees also display irregular anogenital swelling, especially during the early months of gestation [Yerkes & Elder, 1936;Clark & Birch, 1948;van Lawick-Goodall, 1968;Wallis, 1982;Wallis & Lemmon, 19861. The hormonal mechanism involved in anogenital swelling during pregnancy is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SAVAGZ-RUMBAUGH and WILKERSON (1978) reported that an adult P. paniscus female in captivity copulated at all phases of swelling. A laboratory study on 13 P. troglodytes females demonstrated that copulations occurred in all physiological states, except during lactation (LEMMON & ALLEN, 1978). SAVAGE-RUMBAUGH and WILKERSON (1978) also found that a caged P. troglodytes female copulated with a P. paniscus male throughout the swelling cycle.…”
Section: Discussionmentioning
confidence: 98%
“…Again, as noted earlier, the elaborate periovulatory sexual swellings of Pan are an integral component of intense sperm competition, which hominids clearly lack. Moreover, whereas the loss of mammary cyclicity would be unlikely to evolve in Pan [copulation with lactating females is rare (99)], crypticism would not be a barrier in a context of copulatory vigilance within pair bonds (32,79). Moreover, elimination of cyclicity would protect a provisioning (and thereby heavily invested) male from cuckoldry, because prominent mammaries would discourage interest by extra-pair males.…”
Section: Owen Lovejoymentioning
confidence: 99%